Postpartum cortical venous thrombosis: An unusual presentation of postdural puncture headache - Opal Raj; Madhumani Rupasinghe (Journal of Obstetric Anaesthesia and Critical Care, 2016)
Headache is a common occurrence during pregnancy. A postural headache is invariably considered to be a postdural puncture headache in patients who receive neuraxial anesthesia with or without obvious or incidental dural puncture. Cerebral venous thrombosis (CVT) is rare in pregnancy and in the postpartum period, with an incidence of 1:10,000–1:25,000. Pregnancy-induced changes in coagulation result in a hypercoagulable state, which may naturally reduce the incidence of postpartum hemorrhage, but may also increase the risk of CVT. Postpartum headache being frequently encountered may complicate the diagnosis of CVT. We report a case of a woman who developed a postpartum CVT after an accidental wet tap and intrathecal catheter placement during labor.